ADAPTIVE SELLING CAPABILITY DAN KINERJA PENJUALAN PADA PERUSAHAAN FARMASI DI KOTA SEMARANG - Hastuti, Yenny Widya (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2015)
Thepurpose of this research is to test the influences of individual orientation value and sa/esman competence on adaptive selling capability to increase sales performance. Using these variables, the usage of these variables are ab/e to solve the arising problem within phaanacy industry at Semarang city.The samples size of this research is 100 salesman pharmacy industry at Semarang cify. Using the Stmctural Equation Modeling (SEM). The results show that the individual orientation value and salesman competence on adaptive selling capability to increase sales performance.The effect of individual orientation value on adaptive selling capability are significant; The effect of salesman competence on adaptive selling capability are significant; The effect of indtvidual orientation value on sales performance are significant; Tne effect of salesman competence on sales performance are significant,â€™ and The effect of adap[ive selling capability on sales performance are significant;Â